2023
DOI: 10.3390/ijms24108901
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes in Cytokine and Chemokine Receptors in Association with Melanoma Liver Metastasis

Abstract: Cytokines and chemokines (chemotactic cytokines) are soluble extracellular proteins that bind to specific receptors and play an integral role in the cell-to-cell signaling network. In addition, they can promote the homing of cancer cells into different organs. We investigated the potential relationship between human hepatic sinusoidal endothelial cells (HHSECs) and several melanoma cell lines for the expression of chemokine and cytokine ligands and receptor expression during the invasion of melanoma cells. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
1
3
1
Order By: Relevance
“… 12 However, a previous study emphasized the overexpression of the IL11RA gene in the organ‐specific metastasis of primary melanoma cells to the liver, indicating its involvement in the interaction between liver endothelial and melanoma cells. 13 Our study found elevated IL11RA expression in various human SKCM cell lines compared to normal cells. IL11RA downregulation significantly inhibited the migratory and invasive capabilities of SKCM cells.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“… 12 However, a previous study emphasized the overexpression of the IL11RA gene in the organ‐specific metastasis of primary melanoma cells to the liver, indicating its involvement in the interaction between liver endothelial and melanoma cells. 13 Our study found elevated IL11RA expression in various human SKCM cell lines compared to normal cells. IL11RA downregulation significantly inhibited the migratory and invasive capabilities of SKCM cells.…”
Section: Discussionsupporting
confidence: 46%
“…A cytokine profile analysis revealed lower expression of IL‐11RA in tumor‐positive sentinel nodes compared to tumor‐negative sentinel nodes in melanoma 12 . However, a previous study emphasized the overexpression of the IL11RA gene in the organ‐specific metastasis of primary melanoma cells to the liver, indicating its involvement in the interaction between liver endothelial and melanoma cells 13 . Our study found elevated IL11RA expression in various human SKCM cell lines compared to normal cells.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations